Rabphilin silencing causes dilated cardiomyopathy in a Drosophila model of nephrocyte damage - Estela Selma-Soriano (Nature Portfolio, 2021)
Abstract Heart failure (HF) and the development of chronic kidney disease (CKD) have a direct association. Both can be cause and consequence of the other. Many factors are known, such as diabetes or hypertension, which can lead to the appearance and/or development of these two conditions. However, it is suspected that other factors, namely genetic ones, may explain the differences in the manifestation and progression of HF and CKD among patients. One candidate factor is Rph, a gene expressed in the nervous and excretory system in mammals and Drosophila, encoding a Rab small GTPase family effector protein implicated in vesicular trafficking. We found that Rph is expressed in the Drosophila heart, and the silencing of Rph gene expression in this organ had a strong impact in the organization of fibers and functional cardiac parameters. Specifically, we observed a significant increase in diastolic and systolic diameters of the heart tube, which is a phenotype that resembles dilated cardiomyopathy in humans. Importantly, we also show that silencing of Rabphilin (Rph) expression exclusively in the pericardial nephrocytes, which are part of the flies' excretory system, brings about a non-cell-autonomous effect on the Drosophila cardiac system. In summary, in this work, we demonstrate the importance of Rph in the fly cardiac system and how silencing Rph expression in nephrocytes affects the Drosophila cardiac system.